The Professional and Pedagogic Competences of English Teachers With Different UKG (Teaching Competence Test) Achievement Levels - Aisyah, Iis Siti; Yuliasri, Issy; Warsono, Warsono (English Education Journal, 2019)
Professional and pedagogic competences are the basic aspects for effective teaching and learning to take place in classrooms. They are dealing with the quality of teaching-learning process. However, the average score of UKG (Teacher Competence Test) in Indonesia did not achieve standard expected target. This mixed-methods study is aimed to reveal professional and pedagogic competences of English teachers with different UKG achievement levels. Quantitative method was employed in the first phase through student questionnaire to investigate students’ perception on their English teachers’ professional and pedagogic competences performed in classrooms. 14 classes students of six junior high schools in Bandung, West Java, were chosen as participants.The total number of students was 474 with 14 English teachers as subjects of the study. In the second phase, this study employed a descriptive qualitative method through classrooms observation and documentation to reveal how English teachers with different UKG chievement levels performed their competence in classrooms. Five teachers out of the 14 teachers under study were chosen as participants.The finding reveals that based on students’ perception, professional and pedagogic competences demonstrated by English teachers in classrooms do not fully reflect their UKG achievement levels. In some aspects, the teachers with lower UKG achievement are not perceived worse than those with higher UKG achievement. This finding is in line with the finding based on classrooms teaching performance of the five English teachers’ under study. In some parts of lessons, the lower achievers could even perform better than the highers.